Comparison of standard versus tailored parenteral nutrition in paediatric intensive care. Issue 5 (22nd April 2012) - Isaac, R; Reynolds, F; Lewis, C
Abstract : Objective: Patients in paediatric intensive care (PICU) are often fluid restricted and require a high volume of intravenous infusions, allowing little volume for nutritional intake. Bespoke parenteral nutrition (TPN) is associated with higher costs and increased staff time compared with use of standard TPN. This study looks at the desired, prescribed and actual nutritional intake of patients having parenteral nutrition on PICU. Would a standard TPN formulation improve the nutritional intake for these patients? Method: Patients with central venous access requiring TPN on PICU were included in the data collection; patients receiving any enteral intake were excluded. Weight, fluid allowed, TPN prescription, TPN intake, volume of continuous infusions and reasons for withholding TPN were recorded. The desired calorific intake was calculated using values from the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) TPN guidelines. A proposed standard PICU TPN bag formulated was compared with actual intake of the patients included the study. Results: 16 patients with a mean of 4.24 kg (range 0.88–18 kg) received 159 days of parenteral nutrition during the data collection period. Over two thirds of TPN days allowed 100% maintenance fluid or above to be given, however on 42 (26.4%) days the patients were restricted to less than 80% of normal daily fluid allowance. On 62 TPN days the patients were receiving over 10% of their allowed fluid intake as drug infusions. The mean daily fluid allowance given as TPN was 74% of the prescribed fluid allowance. On 62 (38.9%) TPN days over 95% of the prescribed TPN was delivered to the patient, however on 41 (25.7%) days less than 80% of the prescribed TPN reached the patient. Only 66 (41.5%) TPN days provided the desired nutritional intake, 42 days provided between 80 and 95% of the patients required intake and on 51 TPN days the patient received less than 80% of their desired nutritional intake. In 43 of the 51 TPN days where less than 80% of the desired intake was achieved, the proposed PICU standard bag could have been fully administered. More calories would have been delivered on each of the 51 days. Conclusion: The calories a PICU patient prescribed TPN frequently does not provide the desired nutritional intake due to a number of factors. This study shows that a fluid restricted PICU patient will receive more calories from a standard TPN bag than a bespoke formulation; and this may provide financial and productivity savings for PICU.